2013
DOI: 10.1039/c3tc00575e
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the synthesis of ZnO nanomaterials for varistor devices

Abstract: adZnO based varistors are widely used for overvoltage protection in many electrical and electronic circuits, at voltages ranging from a few to over a million volts. By careful control of the microstructure, through nanostructuring by chemical routes, it should be possible to produce varistors with high breakdown voltage (V c ), as this is proportional to the number of active grain boundaries in the sintered body. This property is particularly important for the production of the small-sized varistors needed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(66 citation statements)
references
References 126 publications
(304 reference statements)
3
60
0
Order By: Relevance
“…Zinc oxide (ZnO), a wide band gap semiconductor (3.37 eV), has a vast range of applications which include but are not limited to photocatalysts [8], varistors [9,10], pharmaceutical products [11], and lasers [12]. As a photocatalyst, in the presence of UV radiation, ZnO facilitates production of reactive oxygen species (ROS) on its surface [13].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide (ZnO), a wide band gap semiconductor (3.37 eV), has a vast range of applications which include but are not limited to photocatalysts [8], varistors [9,10], pharmaceutical products [11], and lasers [12]. As a photocatalyst, in the presence of UV radiation, ZnO facilitates production of reactive oxygen species (ROS) on its surface [13].…”
Section: Introductionmentioning
confidence: 99%
“…The breakdown voltage was measured at 1.0 mA/ cm 2 . The nonlinear exponent (a) is defined by a = (logJ 2 -logJ 1 )/(logE 2 -logE 1 ) [15], where E 1 and E 2 are the breakdown voltages responding to J 1 = 0.1A/ cm 2 and J 2 = 1A/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, numerous studies are suggesting the grain boundary phenomena Of ZnO-Bi 2 O 3 and ZnO-V 2 O 5 based ceramic systems studied the influence of MnO 2 , PbO and a mixture of MnO 2 , PbO and B 2 O 3 on electrical and dielectric properties of ZnO-V 2 O 5 ceramics by alternating current (AC) impedance and variable temperature dielectric spectroscopy and found that the Schottky barrier present at grain boundary is much more important for varistor performance [10][11][12]. The electrical conductivity of Mn doped and Co doped ZnOBi 2 O 3 varistors were investigated using complex plane modulus analysis and found that the ratio of grain boundary to grain resistance of Mn doped samples is higher than that of Co doped samples [13].…”
Section: Introductionmentioning
confidence: 99%